VB.net Web developer's guide - Wakefield, Cameron; Sonder, Henk-Evert. (Rockland, Mass. : Syngress Media ; London : International Thomson, 2001)
Visual Basic has long been the language of choice when designing Windows-based applications and the Web. Touted as both the most popular and productive computing language, Visual Basic has amassed quite a following of devoted programmers, and is a sought after programming skill. With the introduction of .NET Enterprise, Microsoft launch VB.NET, offering a streamlined, simplified version of Visual Basic language. With increased power, scalability, functionality and reliability, VB.NET is positioned to be the most productive tool in a programmer's toolbox. VB.NET Developer's Guide is written for previous Visual Basic Programmers looking to harness the power of the new features and functionality incorporated in Visual Basic.NET. Timely coverage of newly released product which Visual Basic users will be eager to learn VB.NET Developer's Guide is one of the first comprehensive reference for programmers and developers anxious to learn about the new technology You can take it with you. The book comes with Syngress' revolutionary Wallet CD containing a printable HTML version of the book, all of the source code examples and demos of popular VB to VB.NET upgrade and programming tools.
Includes index.
Keywords: Microsoft Visual BASIC; Visual programming (Computer science).; Web site development; Electronic books